The growth of knowledgeintensive entrepreneurship in India, 1991 - 2007 - Sunil Mani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
There is enough consensus to show that India's economic performance since 1991 is a direct result of the economic liberalization measures that have been put in place. One of the outcomes of this improved performance is the growth of innovations in the country. This was accompanied by or caused by the emergence of a number of technology-based enterprises. This paper takes a critical look at the available quantitative evidence on the growth of knowledge or technology-based entrepreneurship. It then looks at five facilitating factors for the emergence of this phenomenon in terms of the existence of increased market opportunities, availability of financial support schemes in the form of venture capital funds, existence and enlargement of a number of government programmes, a number of private sector initiatives and education, and training leading to the supply of technically trained personnel. The paper concludes with certain policy suggestions for the continued sustenance of this activity.
Keywords: L26; O16; O30; P12; 330; knowledge-intensive entrepreneurship; knowledge process outsourcing venture capital; angel financing; business incubators; Unternehmensentwicklung; Entrepreneurship-Ansatz; Wissensmanagement; Indien